Modulation of Acupuncture at Quchi (LI 11) and Waiguan (SJ 5) acupoints on LTP-like Plasticity - Qianqian SUN; Guo YU; Huitian ZHANG; Xiaokuo HE (康复学报)
Objective:To explore the effects of acupuncture at unilateral Quchi (LI 11) and Waiguan (SJ 5) acupoint on the bilateral motor cortex (M1) long term potentiation (LTP) -like plasticity in healthy volunteers throughout all the treatment process.Methods:A total of 18 healthy volunteers participated in the study, with acupuncture Quchi (LI 11), Waiguan (SJ 5) acupoint at the region of the right hand, which was conducted on each point until the sensation of Deqi (a characterstic sensation of aching and tingling) was reported by the subjects. Motor evoked potential (MEP) amplitudes induced by transcranial magnetic stimulation (TMS) over the bilateral M1 were measured throughout the whole treatment process, including before acupuncture (15 min), the needle in situ (30 min) and the needle removal (20 min), the unilateral acupuncture effect on LTP-like plasticity induced by PAS was explored. Procedures:①Induced TMS-MEP: The scalp site at which MEPs were elicited in the FDI muscle at the lowest stimulus strength was determined. Fix the coil, Once the optimal scalp site was found, the coil was securely fixed in place by an appropriate mechanical device. We used three laser pens to locate and mark with a soft-tipped pen to assure a constant placement of the coil throughout the session.②Detection of resting motor threshold (rMT): The response resting motor threshold (rMT) was defined as the stimulus intensity at which 5/10 consecutive single stimuli at the optimal sclap site evoked a MEP of at least 50 μV amplitude in the relaxed muscle.③Investigate the short-latency somatosensory-evoked potentials (SLSEP): Monophasic electrical stimulation adjusted to produce visible thumb twitch was delivered at points overlying the ulnar nerve at the right of FDI, through a bipolar electrode (cathode proximal) with intensity 5-10 mA.④Brain plasticity induced by PAS-LTP: The LTP-like plasticity induced by paired associative stimulation (PAS) consisted of 200 stimulus pairs of electrical stimulation followed by TMS. Subjects would be tested 8 times for about 80 minutes each time. The interval of one week was needed to eliminate the interference caused by the post-acupuncture effect.Results:①Compared with before acupuncture, the mean MEP amplitudes used contralaterally to the acupuncture sites were decreased when the needle in situ (P<0.01), while the ipsilaterally MEP amplitudes were increased the mean MEP amplitudes (P<0.01). The MEP amplitudes used bilaterally were increased MEP amplitudes after the needle removal (P<0.01).②After induced by PAS, significant changes were found both contralateral and ipsilateral acupuncture sizes compared to baseline (P<0.01). The results indicated that acupuncture could modulate the LTP-like plasticity of M1.Conclusion:Acupuncture with unilateral Quchi (LI 11) and Waiguan (SJ 5) acupoint could modulate the excitability as well as the LTP-like plasticity of the bilateralized M1 in healthy volunteer, including the needle in situ and the needle removal.